The Role of Hepcidin on Iron and Ferritin Levels in Hemodialysis Patients - Naghdbishi , Hamed; Amerian , Monire; Rafiee, Hoofar; Sarkheyl , Elnaz; Abbaszadeh , Maryam; Sohrabi, Mohammad Bagher (Shahroud Journal of Medical Sciences, 2025)
Background: Anemia is a common complication in dialysis patients, the most important of which are decreased erythropoietin, iron deficiency, blood loss, dialysis, and chronic inflammation. Hepcidin plays a key role in iron homeostasis in dialysis patients and acts as a natural regulator of hemostasis. Given the importance of the subject and the high frequency of iron homeostasis disorders in hemodialysis patients, as well as the lack of sufficient documentation in this regard, the present study aimed to the role of hepcidin on iron and ferritin levels in hemodialysis patients in Shahroud city in 2024.Methods: This study was a descriptive-analytical study that was conducted cross-sectionally on hemodialysis patients in Shahroud city at Imam Hossein Hospital during 2024. In this plan, after initial measures and obtaining written and informed consent, eligible patients were asked to stop taking iron compounds two weeks before the study and not to use any iron supplements without coordination with the administrators. For all patients, iron factors and ferritin were measured using standard laboratory methods, and then hepcidin was measured using ELISA.Results: In the present study, out of 85 patients studied, 45 (52.9%) were male and 40 (47.1%) were female. The mean age of the patients was 54.31±12.59 years (28-79 years). The mean hepcidin level was 60.39±4.22 mg/dL. It was also found that the level of hepcidin was significantly associated with the duration of dialysis (P-value=0.001) and the number of dialysis sessions per week (P-value=0.006) and had no significant relationship with other variables.Conclusion: The results of this study showed that there was a significant relationship between hepcidin levels, dialysis duration, and the number of dialysis sessions per week. It is necessary to control iron levels before starting hemodialysis, and to adjust the dialysis program for each patient specifically.